Assessment and Feedback to Enhance Online English Language Learning - Rizky Eka Prasetya; Achmad Syarif (Universitas Tidar, 2022)
The COVID-19 pandemic has promoted online learning-teaching on a large scale. During the pandemic, English language learners could not complete their learning in the traditional class. To maintain learners learning, most universities have adopted online teaching. Assessment and feedback are critical components of instructional scaffolding, particularly in the online learning environment. These components highlight how English language learners can aid in accomplishing learning objectives and developing self-regulated experiences. This study aimed to explore the design of assessment and feedback of online teaching activities and online teaching processes adopted by English lecturers during the pandemic. The ethnographic case study design is the framework to outline qualitative research. This thematic approach confirms the qualitative researcher’s active participation in identifying assessment and feedback patterns in enhancing English language learners. Given the complexity of assessing and feedback, the study discovered that assessing and feedback could enhance learning English in online situations. These are included the specification of 15 characterizations of the assessment aspect, 15 recommendation elements for conducting the online assessment, and 10 practical online feedback features. The description assessment and feedback remain inextricably and undeniably connected. Online feedback means to be the English lecturers’ reaction to an English learner’s performance.